Maximizing analytical precision: exploring the advantages of ratiometric strategy in fluorescence, Raman, electrochemical, and mass spectrometry detection - Madhu, Manivannan; Santhoshkumar, S.; Tseng, Wei-Bin; Tseng, Wei-Lung (Frontiers in Analytical Science, 2023)
Ratiometric strategy are an invaluable method that helps to detect and quantify analytes. This approach relies on measuring changes in the ratio of two or more signals to improve the accuracy and sensitivity of the results. Ratiometric strategies are widely used in a variety of fields including biomedical, environmental monitoring and food safety. It is particularly popular when traditional single-signal based detection methods are not feasible, especially when interfering substances severely affect the detection. In addition, ratiometric methods have the potential to improve the accuracy and reliability of analyte detection, leading to better results in a variety of complex environments. The article provides a comprehensive review of ratiometric strategy, focusing on ratiometric fluorescent nanoprobes for the visual detection of analytes. This paper also discusses the design of ratiometric two-photon fluorescent probes for biomedical imaging, the synthesis of ratiometric surface-enhanced Raman scattering nanoprobes for the imaging of intracellular analytes, the development of ratiometric molecularly imprinted electrochemical sensors for detection of electroactive species, and the use of isotopically-labeled internal standards in matrix-assisted laser desorption/ionization for ratiometric analysis. The article not only discusses each technique in detail, including its principles, advantages, potential applications, and limitations, but also highlights recent advances in each method and possible future directions.